PERIMBANGAN PEMBERIAN KALIUM DAN MULSA DALAM RANGKA MENINGKATKAN PERTUMBUHAN DAN PRODUKSI CABAI - Bahar, Edward; Gunawan, Ikhsan (E-Journal Sungkai, 2012)
Chilli (Capsicum annuum L) is one of the horticultural crops that are used for domestic purposes as seasoning, food industry and medicine.. This research was carried out village Tranmigrasi DU SKPC sub-district Rambah Hilir regency Rokan Hulu. The reason the research is made in place is because source of water and labor in the region there is. This study is a factorial experiment which consists of two factors with each of the four factorsand six replications were carried out in completely randomized design (CRD).